Peningkatan Wawasan Masyarakat Desa Suco Mengenai Gizi Sayuran Melalui Pelatihan Budidaya Tanaman Pekarangan - Alwi, Annisa Lutfi; Wardana, Rudi; Asmono, Sepdian Luri; Olivia, Zora; Setyoko, Ujang; Wilujeng, Elly Daru Ika (Jurnal Pengabdian Masyarakat Berdampak, 2026)
Suco Village is located in Mumbulsari District, Jember Regency, with a total population of 12,604 people. This makes Suco Village the second most populous village among the seven villages in the district. The high population has resulted in increasingly limited agricultural land, resulting in a decline in food crop production, particularly vegetable production. To address this issue, a proposal was made to develop vegetable cultivation by optimizing the use of home gardens as alternative planting areas. The purpose of this community service activity was to provide education and assistance to PKK women regarding environmentally friendly, easy-to-implement yard use and support family food security. A total of 12 participants enthusiastically participated in the counseling, demonstrations, and hands-on practice of planting vegetables in their home gardens using simple methods such as vertical cultivation and polybags. Based on the post-test results, there was an increase in community knowledge about vertical cultivation by 97.8%, knowledge of drip irrigation systems by 123.7%, and understanding of economic and environmental benefits by 80.4%. This proves that the training activity succeeded in transferring knowledge effectively. High post-test scores indicate that participants not only received the information but were also able to understand the theory and practice provided well.